Perjanjian Iklan di Radio Suara Akbar Surabaya menurut Hukum Islam dan Hukum Positif - Alifia Nisa Ikbar (Maliyah : Jurnal Hukum Bisnis Islam, 2020)
The data of this research were collected using observation, interview, and literature study techniques. Then analyzed with descriptive techniques in describing the problem of advertising agreements at Radio Suara Akbar Surabaya. After the data obtained were then analyzed using the Islamic Law and Positive Law. The results of this study concluded that the advertising agreement on SAS FM radio Surabaya with the advertiser, namely the Al Falah Social Fund Foundation (YDSF) had no procedural problems, but in practice there was a default by SAS FM radio with the broadcaster's negligence in managing the time. So that, the advertisement cannot be played as agreed, namely at the exact time of the SAS FM radio signal, in addition to an erratic power outage, and an unexpected time transmitter malfunction. The advertising agreement in this case, according to Islamic law, there are conditions that are not fulfilled, so that it is detrimental to the YDSF advertiser whose advertisement is not shown at the right time signal. According to positive law, it also causes losses to the party carrying out the advertisement. So that, the advertiser can claim compensation for both broadcast time and costs. In this case, the aggrieved party is the client by not showing the advertisement as agreed, then SAS FM is required to change the broadcast time outside the existing agreement.